EMPLOYER BRAND PERCEPTIONS : The role of applicant´s identity - Laakso, Saku (My University, 2021)
Previous academic research uses the concept of Talent War to describe the situation in the labour market and employer branding activities targeted to university students and future professionals. A shortage of talents is a global problem and especially experts in demanding work require activities in the field of employer branding. As different people require different activities, it is necessary to find out how the recipients of these activities perceive their ideal employer brands. Academic research uses employer brand concepts in different ways, and this is a challenge for the rather new research field. This exploratory research studies ideal employer brand perceptions among university students from Finland, Sweden, and United Kingdom. The research´s aim is to find out how identity, divided in personality and social identity in this research, influences these perceptions. The data of 5090 respondents were included in the study that applied a relatively new research method called mixed method research to find out these perceptions. The research results indicate that identity has significant influence on how university students perceive their ideal employer brands. It is visible that students are interested in expressing their identity to others and employer brand image offers a tool for this purpose. Similar personality characteristics, which students possess themselves, are found in students´ ideal employer brands. Social identities, indicated in this research as nationality, had significant differences regarding perceptions. Students perceive symbolic attributes considerably more compared to instrumental attributes regarding their ideal employer brands, and symbolic attributes related to innovativeness is the most perceived one. Business managers, working in employer branding, should take into account applicants´ natural need for self-expression. Similarly, this research´s managerial implications include that significant differences exists in ideal employer brand perceptions based on identity, the role of symbolic meanings in ideal employer brand perceptions is important, and there is a connection between employer brand and company´s product and services.

Aiempi tutkimus käyttää termiä ’osaajasota’ kuvatessaan työmarkkinoiden tilannetta, sekä työnantajabrändäystoimia korkeakouluopiskelijoille ja tulevaisuuden ammattilaisille. Tällä hetkellä vallitsee globaali pula osaajista. Erityisesti haastavissa tehtävissä toimivien asiantuntijoiden houkuttelu työpaikkoihin vaatii erilaisia toimenpiteitä työnantajabrändäyksen toimialalla. Erilaisten ihmisten houkuttelu hakemaan työpaikkoihin vaatii erilaisia toimia, joten on tarpeen selvittää, miten näiden toimien kohteet hahmottavat ideaalityönantajabrändinsä. Akateeminen tutkimus käyttää työnantajabrändäykseen liittyviä termejä eri tavoin. Tämä on haaste suhteellisen uudelle tutkimusalalle. Tämä eksploratiivinen tutkimus tutkii ideaalityönantajabrändien hahmotuksia korkeakouluopiskelijoiden keskuudessa, kohdemaina Suomi, Ruotsi ja Yhdistynyt kuningaskunta. Tutkimuksen tarkoituksena on selvittää miten identiteetti, jaettuna tässä tutkimuksessa persoonallisuuteen ja sosiaaliseen identiteettiin, vaikuttaa näihin hahmotuksiin. Tässä tutkimuksessa hyödynnetään 5090 vastaajan dataa. Tutkimus käyttää suhteellisen uutta tutkimusmetodologiaa nimeltä monimenetelmätutkimus selvittääkseen näitä hahmotuksia. Tutkimustulokset osoittavat, että identiteetillä on merkittävä vaikutus siihen, miten korkeakouluopiskelijat hahmottavat ideaalityönantajabrändejänsä. Opiskelijat ovat kiinnostuneita ilmaisemaan identiteettiään muille, ja työnantajaimago tarjoaa työkalun tähän tarkoitukseen. Opiskelijoiden ideaaleissa työnantajabrändeissä on havaittavissa samanlaisia persoonallisuuspiirteitä, kuin he omaavat itse. Sosiaalisten identiteettien, indikoituna tässä tutkimuksessa kansallisuutena, välillä on merkittäviä eroja hahmotuksiin liittyen. Opiskelijat hahmottavat ideaalityönantajabrändeihinsä liittyviä symbolisia aspekteja paljon enemmän verrattuna instrumentaalisiin puoliin. Symboliset aspektit, jotka liittyvät innovatiivisuuteen ovat kaikkein hahmotetuimpia. Yritysjohtajien, jotka työskentelevät työnantajabrändäyksen parissa, tulisi ottaa huomioon hakijoiden luontainen tarve itsensä ilmaisemiseen. Tämän tutkimuksen liikkeenjohdon suosituksiin lukeutuvat lisäksi huomattavat erot ideaalityönantajabrändien hahmotuksissa identiteettiin perustuen, symbolisten merkitysten rooli ideaalityönantajabrändien hahmotuksissa on tärkeä ja työnantajabrändin ja yrityksen tuotteiden ja palveluiden välillä vallitsee on yhteys.
Keywords: Employer brand, Employer Brand Image, Social identity theory, Instrumental-Symbolic Framework